Information Externalities Affecting the Dynamic Pattern of Foreign Direct Investment : The Case of China - Shirai, Sayuri (IMF Working Papers; Working Paper ;, 1994)
The dynamic pattern of foreign direct investment (FDI) in developing countries shows a three-phase pattern. Despite government policies that promote it, initially the inflow of FDI is sluggish, followed by a period of considerable fluctuation before finally entering the stage of rapid growth. The paper explains the pattern through recourse to two concepts: the searching process of individual investors and the information externalities of investors in the aggregate. Policy implications that may serve to shift an economy of a developing country from small-scale FDI to one of rapidly expanding FDI are considered. As China is a clear example of this pattern, it has been selected to promote understanding of the process.